Challenges of Pedagogical Supervision in the Contemporary Educational Context - Wallace de Freitas Oliveira; Edwin Cardoso Neves; Paula Cristina Pelli Paiva; Haroldo Neves de Paiva; Amaro Ilídio Vespasiano Silva (Archives of Current Research International, 2025)
Aims: This study aimed to analyze the main challenges faced by pedagogical supervision in the current educational context, highlighting its role across different levels and modalities of education. Study Design: Descriptive narrative literature review. Methodology: A search was conducted covering the last five years in the SciELO and CAPES Portal databases, as well as in the gray literature through Google Scholar. The descriptors used were “pedagogical supervision,” “teacher training,” and “higher education,” combined with the boolean operator AND. After applying inclusion and exclusion criteria, eight studies were selected, all from scientific journals. Results: The findings reveal that pedagogical supervision still faces significant challenges, such as the lack of clear guidelines, excessive workload assigned to supervisors, and a shortage of ongoing training. In many contexts, practices are still rooted in directive and bureaucratic models focused on control and inspection, which limits their formative potential. Furthermore, structural factors such as lack of resources and institutional fragility hinder the effectiveness of supervisory actions. However, more recent experiences indicate a gradual shift toward more dialogical and collaborative approaches that emphasize active listening, teamwork, and continuous pedagogical support for teachers. In this transition, Information and Communication Technologies (ICTs) play a strategic role, strengthening communication among educational stakeholders, enabling the monitoring of pedagogical practices, organizing data, and facilitating online training. Conclusion: It is concluded that pedagogical supervision must be redefined as a formative and supportive process, requiring public policies that invest in supervisor training, technological resources, and structures for professional development.